The Development Of Physics Module With The Scientific Approach Based On Islamic Literacy. (February 2019) - Diani, R; Kesuma, G C; Diana, N; Yuberti,; Anggraini, R D; Fujiani, D
Abstract: The result of observation conducted at Islamic Senior High School (MA) Da'ar Al Hikmah Seputih Mataram and Senior High School (SMA) 10 Bandar Lampung indicated that a literacy-based learning material is needed. This study aims to develop a physics literacy-based learning module using the scientific approach. This development research applies the 4D model which only consisted of three stages, namely define, design, and develop. The result of module validation shows that the developed module is in the highly feasible category. Furthermore, the response of teachers and students toward the module indicates that the developed module is in a very interesting category. Thus, the developed physics learning module with a scientific approach and Islamic literacy-based can be used as a support for learning physics in school.